Lenvatinib Combined With a PD-1 Inhibitor as Effective Therapy for Advanced Intrahepatic Cholangiocarcinoma - Xie, Lulu; Huang, Jingzheng; Wang, Linling; Ren, Wenrui; Tian, Hao; Hu, Anhong; Liang, Jun; Jiao, Yuqing; Li, Yali; Zhou, Qunfang; Zhang, Wenjing (Frontiers in Pharmacology, 2022)
Background: Lenvatinib combined with a PD-1 inhibitor has obtained a satisfactory antitumor effect in several solid tumors. However, the efficacy and tumor response of lenvatinib with a PD-1 inhibitor in advanced intrahepatic cholangiocarcinoma still need further exploration. Methods: This is a single-arm study for the assessment of the efficacy and tolerability of lenvatinib with a PD-1 inhibitor in intrahepatic cholangiocarcinoma patients who had chemotherapy failure. Efficacy was evaluated based on the Response Evaluation Criteria in Solid Tumors RECIST Version 1.1 (RECIST 1.1). Results: A total of 40 patients with advanced intrahepatic cholangiocarcinoma were enrolled after the chemorefractory effect. The median progression-free survival was 5.83 ± 0.76 months. The 3-month and 6-month progression-free survival rates were 80.0% and 32.5%, respectively. The median overall survival was 14.30 ± 1.30 months. The 12-month and 18-month overall survival rates were 61.4% and 34.7%. The 3-month RECIST 1.1 evaluation was that seven patients (17.5%) showed partial response, 23 patients (57.5%) had stable disease, and 10 patients (25.0%) had progressive disease. The objective response rate was 17.5%, and the disease control rate was 75.0%. All the recorded any-grade adverse events inducing treatment termination were controllable, and there were no AE-related deaths. Conclusion: Our study showed that a combination of lenvatinib with the PD-1 inhibitor could be an effective treatment for advanced intrahepatic cholangiocarcinoma after the chemorefractory effect.